Socio- Economic Problem Faced by Women Headed Family in Resettled People of Karainagar - Srikanthan, S. (University of Jaffna, 2011)
At present, women headed families increased in the third world country due to the war and it is becoming an important social problem. Women are mostly affected and victimized through the war in these countries. We have to analyses the socio -economic problem faced by women headed families to promote our regional economic development In the post war period of Sri Lanka. The phenomenon of development has emerged as multifaceted and multifarious paradigms. The concepts of Gender and development, development in gender and gender in development have emerged an importance concept in socio – economic field after the Second World war period. This study attempts to bring out the socio – economic problem of the women headed families of karainagar resettled from wanni welfare center in the post war period. This study has adopted social anthropological research methods. 584 families have resettled by the government but 92 families are women headed families. As the perception on women made through the cultural ideology, the women have to face many social problems regarding their economic activities. In this context, we must study the problem of resettled women headed families and women should be so as to encourage the participating in their livelihood activities. In this research, Secondary data is collected from the records of assistant government agent office and Grama sevar office, while the primary data is collected through the interview, case study and questionnaire. Questionnaire will be issued 30 percentages of families on the selected on sampling basis. Through this study we attempt to suggest the program of action to minimize the economic problems faced by women headed families.
Keywords: livelihood development; resettlement; gender development